Health Assessment Questionnaire-Disability Index (HAQ-DI) use in modelling disease progression in diffuse cutaneous systemic sclerosis: an analysis from the EUSTAR database. - Allanore, Yannick; Bozzi, Sylvie; Terlinden, Augustin; Huscher, Doerte; Amand, Caroline; Soubrane, Christina; Siegert, Elise; Czirjak, Laszlo; Carreira, Patricia E.; Hachulla, Eric; Zanatta, Elisabetta; Li, Mengtao; et al. (Arthritis Research & Therapy, 2020)
BACKGROUND: Patients with diffuse cutaneous systemic sclerosis (dcSSc) have a poor prognosis. The importance of monitoring subjective measures of functioning and disability, such as the Health Assessment Questionnaire-Disability Index (HAQ-DI), is important as dcSSc is rated by patients as worse than diabetes or hemodialysis for quality of life impairment. This European Scleroderma Trials and Research (EUSTAR) database analysis was undertaken to examine the importance of impaired functionality in dcSSc prognosis. The primary objectives were to identify predictors of death and HAQ-DI score progression over 1 year. HAQ-DI score, major advanced organ involvement, and death rate were also used to develop a comprehensive model to predict lifetime dcSSc progression. METHODS: This was an observational, longitudinal study in patients with dcSSc registered in EUSTAR. Death and HAQ-DI scores were, respectively, analyzed by Cox regression and linear regression analyses in relation to baseline covariates. A microsimulation Markov model was developed to estimate/predict natural progression of dcSSc over a patient's lifetime. RESULTS: The analysis included dcSSc patients with (N = 690) and without (N = 4132) HAQ-DI score assessments from the EUSTAR database. Baseline HAQ-DI score, corticosteroid treatment, and major advanced organ involvement were predictive of death on multivariable analysis; a 1-point increase in baseline HAQ-DI score multiplied the risk of death by 2.7 (p < 0.001) and multiple advanced major organ involvement multiplied the risk of death by 2.8 (p < 0.05). Multivariable analysis showed that baseline modified Rodnan Skin Score (mRSS) and baseline HAQ-DI score were associated with HAQ-DI score progression at 1 year (p < 0.05), but there was no association between baseline organ involvement and HAQ-DI score progression at 1 year. HAQ-DI score, major advanced organ involvement, and death were successfully used to model long-term disease progression in dcSSc. CONCLUSIONS: HAQ-DI score and major advanced organ involvement were comparable predictors of mortality risk in dcSSc. Baseline mRSS and baseline HAQ-DI score were predictive of HAQ-DI score progression at 1 year, indicating a correlation between these endpoints in monitoring disease progression. It is hoped that this EUSTAR analysis may change physician perception about the importance of the HAQ-DI score in dcSSc.
EVALuna2:347858